Enhancing High School Physics Learning Through Augmented Reality: A Bibliometric and Systematic Review - Tugirin, Tugirin; Kuswanto, Heru; Ramazhoni, Deo Alfitra; Putri, Rahmania Amanah; Muslim, Riyadi; Moore, Jordan Kyle (FKIP Universitas Lampung, 2025)
Enhancing High School Physics Learning Through Augmented Reality: A Bibliometric and Systematic Review. Objective: This study aims to investigate the research trends, opportunities, effectiveness, and challenges of implementing Augmented Reality (AR) technology in physics education through a systematic literature analysis. Methods: This research employed a bibliometric and systematic review approach of 45 selected journal articles obtained from the Scopus database. Data were extracted on May 2, 2025, covering publications from 2020 to 2025. The initial search using the keywords